Exploring the Bereavement Experiences of Older Women with Intellectual Disabilities in Long-Term Residential Care: A Staff Perspective. (October 2014) - Morgan, Nancy; McEvoy, John
This study explores the impact of bereavement on a group of older women with intellectual disabilities who have lived in a congregated residential setting for most of their lives. Using Interpretative Phenomenological Analysis, staffs' experiences of supporting individuals with varying degrees of intellectual disabilities through grief are examined. Data analysis revealed five super-ordinate themes. The findings indicate that recognizing grief in this group is complex, and secondary loss frequent. Carers and relatives may over-protect and disenfranchise their grief which is often expressed through changes in behavior and there may be a time lag before these expressions of grief are noticed. Religious practice and rituals were found to be helpful in coping and adjusting to loss. Carers are important advocates for supporting service users who are grieving, thus information on how grief is processed in elderly individuals with intellectual disabilities has implications for training and educating staff in supporting vulnerable adults.